Concise synthetic approach toward tamiflu (oseltamivir phosphate): cis-aziridine as the key synthon and RCM - Chavan, S. P.; Chavan, P. N.; Khairnar, L. B. (RSC Advances, 2014)
A synthesis of oseltamivir (Tamiflu) was achieved starting from D-mannitol. A unique feature of the synthetic route is that an acyclic precursor was constructed, which was then cyclized in an intramolecular aldol reaction to form the Tamiflu skeleton. Throughout the synthesis, well-established, highly efficient reactions were employed, and no protection/deprotection sequence was needed.